Penggunaan PVD dan Preloading untuk Mempercepat Waktu Konsolidasi Di Lahan Penumpukan Peti Kemas Pelabuhan Trisakti Banjarmasin - Rusdiansyah Rusdiansyah (INFO-TEKNIK, 2008)
Development of extension of heaping container area of The Port Of Trisakti Banjarmasin ( Phase I) for the width of 50 x m 200 m started at year-end 2006, this meant as supporter medium for the increase of service to port user specially container. Of theoretical calculation and aktual in field happened difference of result because usage of data in taken away from theoretical calculation of data investigation of land; ground in the year 2000 while execution of work in the year 2007. During range of time (± 7 year) conducive by elementary land; ground experience of resulted from degradation land weight itself effect and land; ground of existence of influence of work of development of dock in container farm location (heavy equipment traffic and dock material heap). Result of analysis and perception of field as a whole express that natural land; ground of degradation of primary which isn't it however admiting of to experience of small degradation (sekunder degradation).